2007
DOI: 10.1525/srsp.2007.4.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Sex workers, fem queens, and cross-dressers: Differential marginalizations and HIV vulnerabilities among three ethnocultural male-to-female transgender communities in New York City

Abstract: This article describes 3 distinct ethnocultural male-to-female transgender communities in New York City: the low-income African American/Black1 and Latina(o) House Ball community; lowincome, often undocumented immigrant Asian sex workers; and middle-class White crossdressers. These communities are highly socially isolated from each other and are more connected to their ethnocultural contexts than to an abstract and shared transgender identity. Whereas previous research either has viewed male-to-female transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 52 publications
(52 reference statements)
3
89
0
Order By: Relevance
“…Research in Asia and North America, for example, has shown that the broad category 'transgender' may include a diversity of other identities and that HIV risk may differ significantly between these (cf. Chakrapani, Newman, Shunmugam & Dubrow 2011;Hwahng & Nuttbrock 2007).…”
Section: Are There Transgender People In Africa?mentioning
confidence: 99%
“…Research in Asia and North America, for example, has shown that the broad category 'transgender' may include a diversity of other identities and that HIV risk may differ significantly between these (cf. Chakrapani, Newman, Shunmugam & Dubrow 2011;Hwahng & Nuttbrock 2007).…”
Section: Are There Transgender People In Africa?mentioning
confidence: 99%
“…This finding aligns with those reported by Dixen et al (1984), who found that 16.9 % of MtF transsexuals had practiced prostitution. Prostitution has been linked to poverty, poor family financial resources, little or no family support, difficulty finding work, a low educational level (Hwahng & Nuttbrock, 2007), and homosexual orientation (Lawrence, 2010a).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…This was the case not only with the transgender population but also of sex worker sub-populations (Hwahng & Nuttbrock, 2007;Cáceres, Konda, Pecheny, Chatterjee, & Lyeria, 2006). Nevertheless, the term MSM was maintained in the last two proposals, and such generalisation delayed consideration of specific interventions targeting sub-populations, which would have improved the strategies in place.…”
Section: Characterisation Of the Epidemicmentioning
confidence: 99%